SOCIAL INJUSTICE AND RACIAL PREJUDICE IN MAXWELL ANDERSON’S WINTERSET - Eko Budi Setiawan (Humaniora Scientia, 2015)
Winterset is one of the great works of Maxwell Anderson that reveals universal values ​​such as love, hatred, revenge, and also fear. Winterset also describes social events depicted through the lives of the actors who are oppressed. The main problem in this research is related to social injustice and race prejudice. The writer uses sociological approach and historical biographical approach in analyzing the problem. Mio as the main character represents figure from oppressed community and lives in poverty. While Trock Estrella, Judge Gamet reflects a ruler who acts arbitrarily against the poor and oppressed. This study reveals the causes of mistreatment in the field of law and prejudice against race or class. In court, Mio’s father, Romagna was arrested by police for no apparent reason at the time of the robbery, and eventually he was sentenced to death. Although there were witnesses who saw that Romagna did not commit robbery,but nevertheless the judges did not believe Mio and the death sentence was done. In everyday life Mio was not allowed to live in New York but he had to come together with people of other minorities. Mio also did not get the same treatment as the rich people in the field of education for minorities would not be able to pay for school.